The Effect Of The Implementation Of Occupational Health And Safety Management Systems (Smk3) Against Security Tower Construction Project " X ”In Surabaya - Mansur; Fredy Kurniawan; Atik Wahyuni (Neutron, 2021)
This study aims to analyze the effect of the implementation of the Occupational Safety and Health Management System (SMK3) on the productivity of workers on the "X" tower construction project in Surabaya. The population used is the employees of the tower construction project "X" in Surabaya as many as 230 employees, while the number of samples taken 146 employees. The data used is sourced from primary data. Data collection is done by distributing questionnaires. The data analysis technique used is multiple linear regression analysis.The results in this study indicate that: (1) Safety Factor has a significant and positive influence on Project Security; (2) Equipment and Work Wear Factors have a significant positive effect on Project Security; (3) Vehicle Track Factors have a significant positive effect on Project Security; (4) Fire Factor has no significant effect on Project Security; (5) Equipment and Machine Factors have a significant positive effect on Project Security; (6) Electricity and Sound factors have a significant positive effect on Project Security; (7) Public Protection Factors have no significant effect on Project Safeguards; (8) General Factors have a significant positive effect on Project Security; (9) Occupational Health Factors have a significant positive effect on Project Security.